The Stories We Tell: Narratives of Mothering and Work during the Dual Pandemics of 2020 - Dillard, Nicole; Cavallo, Taylor (Journal of the Motherhood Initiative for Research and Community Involvement, 2023)
Narratives remain powerful in shaping both the cultural stories and personal stories that inform our lives. Specifically, narratives concerning mothering and work are particularly powerful not only for women who are balancing professional life and childrearing responsibilities but also for our larger cultural understanding of what and who society has deemed a “working mother” is or should be. The complexities of these narratives were further complicated due to the simultaneous COVID-19 and racism pandemics of 2020 that exposed fractures in some of our most eminent narra-tives around mothering and work. Furthermore, and perhaps most importantly, the recent pandemics illuminated the fact that many of these narratives are incomplete and often exclude, overlook, or erase women of color and other women who occupy marginalized identities as well as the challenges they face. Our goal is to expose the gaps within these narratives against the backdrop of the dual pandemics and explore the historical and social contexts in which other narratives of mothering and work exist for women of color and other women with marginalized identities. Through centering the individual counterstories that challenge problematic narratives, we aim to use these examples to outline optimistic yet realistic possibilities that explore complexities within mothering and work and support learning and social change for a post-pandemic world.